Ways to improve reconnaissance in the interests of missile forces and artillery - Shuliakov , Sergey; Dorofeev , Nikolai (Social Development and Security, 2019)
The article describes the experience of creating automated control systems by foreign countries. Experience in controlling fire weapons and reconnaissance assets. The analysis of their interaction. Considered in detail the automated control system of field artillery of the United States of America Advanced Field Artillery Tactical Data System (AFTDS). This is an experience of creating a system of foreign countries. Experience in controlling fire weapons and reconnaissance assets. The analysis of their interaction. Considered in detail is the United States of America Advanced Field Artillery Tactical Data System (AFTDS). This is a multipurpose tactical information system of field artillery using mobile technology. It provides automated decision making for the functional subsystem, support for the ground forces and marines, as well as integrated operational units and united types of troops. The article describes the entire sector of the capabilities of this automated combat control system. The article also discusses ADLER (Artillerie Daten Lage and Einsatz Rechnerverbund) Germany’s automated field artillery control system. This automated field artillery control system provides all the field artillery control capabilities from the division to the gun (mortar, MLRS, reconnaissance equipment). The unified information network unites target detection facilities, combat (fire) and fire weapons control centers (points). it makes it possible not only to process the data, but also to control the detection mode and hit targets, including the evaluation of intermediate results. Integrated systems of reconnaissance, surveillance, target definitions and their destruction are considered by military experts of the leading, militarily, countries of the world as a critical element for achieving information superiority over the enemy. Analysis of the interaction of artillery reconnaissance forces and weapons and armaments of the leading military countries of the world provides an opportunity to study the development of weapons and military equipment to ensure the creation of an intelligence-information subsystem of artillery.